Equestrian Canada: COVID-19 return to business operations framework (Equestrian Canada, 2020)
This document is designed as a framework for equine and equestrian facilities to develop a return to business operations plan based on protocols provided by provincial and federal health organizations post-pandemic. Facilities that develop a plan based on this framework will be prepared to resume operations as soon as provincial and federal legislation allows.